Ciência e Arte no ensino de Física - Vilar, Artur; Oliveira Ribeiro de Souza , Eduardo; de Almeida Barbosa-Lima, Maria da Conceição (Góndola, enseñanza y aprendizaje de las ciencias, 2025)
In our article, we present reflections on the historical relationship between Science and Art and the possibilities of using this important connection in Science Teaching, with emphasis on what refers to the teaching and learning processes of Physics. We focus the research presented here on three aspects of the eleven existing artistic manifestations, namely: Music, Literature and Comics. We discuss, in this way, the importance of language in classes and how poems, songs and comic strips can be more than just mottos, assuming a prominent role in teaching that values investigation, valorization of dialogism, the search for interdisciplinarity , without disregarding factors such as the historical, critical and social context of these works, their authors, as well as the students and the school environment in which they are inserted. We discussed the use of music and poetry by artists such as Caetano Veloso, Gilberto Gil, António Gedeão and Ferreira Gullar. We present concrete possibilities for using these works in Basic Physics and Modern and Contemporary Physics classes. Likewise, we present some examples of authorial comics or comics from artists such as Laerte and Alexandre Beck so that teachers can influence themselves with a view to developing classes that, in addition to traditional Physics themes, address themes that cover students' daily lives. We intend to contribute, from the perspective of Physics Teaching, with the process of consolidating the recent field of research that has been called Science and Art and which is in a constant process of investigation, reflection and construction with the participation of researchers and artists from the most diverse areas. and strands.